The Study of Law Perspective to Family Relationship andAcademic Performance in Madrasah - General Santos City,Philippines - Canacan, Jebrel C.; , Dr. M. Abdul Kholiq Hasan, M.A., M.Ed; , Dr. Anam Sutopo, M.Hum (2014)
This study would like to find out the law perspective to family relationship academic and performance in Madrasah in General Santos City, Philippines.Specifically, the researcher sought answers to the following questions: 1.What is the level of family relationship that exist among the families of Madrasah in terms of (a) father and mother relationship, (b) parents and children relationship, (c) siblings relationship, and (d) children-relative relationship? 2. What is the academic performance in Madrasah and is there a significant of family relationship to the academic performance in Madrasah in General Santos, Philippines? A total population of 115 Madrasah learners as well as their parents served as respondents in the study. The respondents came from three selected public high schools in the Division of General Santos City during the school year 2013-2014.Family relationships were measured in terms of four parameters namely husband-wife relationship, parent-children relationship, siblings relationship, and children-relative relationship. The academic performance in Madrasah was based on the average grades during the third grading period obtained from their respective teachers. Two major instruments were used in this study: the first questionnaire on family relationship was answered by the parents and the second questionnaire also on family relationship, was answered by the Madrasah learners.The following statistical treatments used were mean, percentage and multiple linear regression analysis at 0.05 level of significance.The result of the study showed that the performance in Islamic Values of Madrasah learners were significantly affected by their family relationship. Specifically, learners performed better when they have smooth, loving and close relationship with their siblings and parents. They also perform better when they have close relationship with relatives, however, do not significantly affect their Islamic Values performance.